Nothing but honour: the story of the Warsaw uprising, 1944 - Muller, V.C. (Scientia Militaria - South African Journal of Military Studies, 2011)
Professor Zawodny, Avery Professor of International Relations at Claremont Graduate School and Domona College, California was an active participant in the events described. Fully documented, the story is based almost entirely on primary sources. Professor Zawodny has consulted German, Soviet, Ukrainian, Polish, British and American documents. Some of them have only recently been declassified and shed new Iight on Soviet-British-American relations during World War II.